Implementation of QCC method to reduce defects in rear combination lamp gaps on MPV vehicles in the automotive industry - Setiawan, Setiawan; Kurnia, Hibarkah; Nasihardani, Dana; Putri, Hana Silvia Dwi (Operations Excellence: Journal of Applied Industrial Engineering, 2025)
The appearance of four-wheeled vehicles is the first aspect observed by customers. Defects in appearance, such as gaps in the rear combination lamps, can reduce the competitiveness of Multi-Purpose Vehicle (MPV) products. Such defects affect product quality and customer satisfaction, making it essential for companies to minimize defects to enhance market competitiveness. This study applies the QCC (Quality Control Circle) method with a PDCA (Plan-Do-Check-Action) approach, supported by the 8-step problem-solving process and 7 QC tools. The method aims to identify the root causes of defects and implement appropriate corrective actions. In its implementation, the Plan phase involves identifying the problem and analyzing root causes using QC tools such as Pareto charts and fishbone diagrams. In the Do phase, corrective actions are carried out by adjusting processes or materials. The Check phase includes evaluating the results of the corrective actions, while the Action phase ensures the changes are sustained over time. Using the QCC method, defect rates per unit decreased from 0.130 to 0.004.